Genomic Insights into the Adaptability of the Spoilage Bacterium Lactobacillus acetotolerans CN247 to the Beer Microenvironment. (2nd January 2023) - Luan, Chunguang; Cao, Weihua; Luo, Na; Tu, Jingxia; Hao, Jianqin; Bao, Yihong; Hao, Feike; Wang, Deliang; Jiang, Xin
Abstract: A novel beer-spoilage bacterium, Lactobacillus acetotolerans, has frequently been encountered in south China beer breweries, imparting an undesirable and unpalatable "buttery" taste and oily mouthfeel to beer. Understanding the genetic basis of spoilage bacterial adaptability to the beer microenvironment is crucial for the proper control of bacteria such as L. acetotolerans CN247 at an industrial scale. In this study, the complete genome of L. acetotolerans CN247 was sequenced using the PacBio and Illumina Miseq high-throughput sequencing technologies, and the relationship between genetic and physicochemical properties was analyzed. The genome size of L. acetotolerans CN247 was found to be 1.677 Mb, with a GC content of 37.55%. A total of 1, 636 protein-coding genes were predicted, accounting for 88.96% of the genome. The average length of coding sequences was 912 bp. The L. acetotolerans CN247 strain was tolerant to high concentrations of acetic acid (6%) and showed varying degrees of preference for different beer components (i.e., sugars such as maltose, ribose, cellobiose, and mannitol). This strain also had a high tolerance for ethanol (14%) in the beer and was resistant to streptomycin, at a minimum inhibitory concentration of 256 μg/mL. Finally, genes associated with viable but non-culturable (VBNC) bacteria were found in the genome of L. acetotolerans CN247. This is the first study reporting the complete genome sequence of L. acetotolerans as a beer spoilage bacteria. These findings will contribute to the understanding of this bacterium's life cycle and help in the improvement of industrial contamination prevention practices. Supplemental data for this article is available online at https://doi.org/10.1080/03610470.2021.1997280 .